Determining Inappropriate Medication Alerts from “Inaccurate Warning” Overrides in the Intensive Care Unit - Rehr, Christine A.; Wong, Adrian; Seger, Diane L.; Bates, David W. (Applied Clinical Informatics, 2018)
Objective This article aims to understand provider behavior around the use of the override reason “Inaccurate warning,” specifically whether it is an effective way of identifying unhelpful medication alerts.Materials and Methods We analyzed alert overrides that occurred in the intensive care units (ICUs) of a major academic medical center between June and November 2016, focused on the following high-significance alert types: dose, drug-allergy alerts, and drug–drug interactions (DDI). Override appropriateness was analyzed by two independent reviewers using predetermined criteria.Results A total of 268 of 26,501 ICU overrides (1.0%) used the reason “Inaccurate warning,” with 93 of these overrides associated with our included alert types. Sixty-one of these overrides (66%) were identified to be appropriate. Twenty-one of 30 (70%) dose alert overrides were appropriate. Forty of 48 drug-allergy alert overrides (83%) were appropriate, for reasons ranging from prior tolerance (n = 30) to inaccurate ingredient matches (n = 5). None of the 15 DDI overrides were appropriate.Conclusion The “Inaccurate warning” reason was selectively used by a small proportion of providers and overrides using this reason identified important opportunities to reduce excess alerts. Potential opportunities include improved evaluation of dosing mechanisms based on patient characteristics, inclusion of institutional dosing protocols to alert logic, and evaluation of a patient's prior tolerance to a medication that they have a documented allergy for. This resource is not yet routinely used for alert tailoring at our institution but may prove to be a valuable resource to evaluate available alerts.
Keywords: computerized provider order entry system; clinical decision support; adverse drug event; patient safety; intensive care units